Optimization of distances measurement by an ultrasonic sensor. (2019) - Rocchi, A.; Santecchia, E.; Barucca, G.; Mengucci, P.
Abstract: The problem of environmental disasters due to oil spills has characterized recent history from first years of '900 and still represents an important risk factor for environmental protection. The equipment and techniques currently in use for monitoring the marine water are very expensive. The scope of this research is the design and optimization of a non-contact ultrasonic sensor system capable of providing the water level in marine environment. This system is a part of a very low-cost device to detect pollution due to the presence of non-conductive liquids (i.e. hydrocarbons floating in the sea), exploiting the different conductivity of the fluids involved. The work focuses on the characterization of the SRF05 ultrasonic, providing the Time Of Flight (microseconds) of transmitted wave which interacts with a surface target, and on its configuration inside a floating organ as a result of data obtained from laboratory tests. Experimental tests were conducted using a micrometric sledge in a climatic chamber, in order to study the effect of the climatic conditions variations, such as temperature and humidity, on the velocity of ultrasonic waves, with the aim to establish the best operating range in terms of sensor resolution and architecture of the buoy. In order to improve the accuracy of the system and to overcome issues linked with the climatic conditions, the adoption of a sensor system consisting of the combination of two SRF05 sensors, is suggested. One of these sensors can detect the speed of sound, based on a fixed distance, while the other should be arranged to detect the water surface. The final device is controlled by an Atmega328P low-power microcontroller through an algorithm, and can detect the level of liquid surface (sea water or contaminant) with sensibility of about 1 mm.